Core-fucosylation plays a pivotal role in hepatitis B pseudo virus infection: a possible implication for HBV glycotherapy. (14th November 2016) - Takamatsu, Shinji; Shimomura, Mayuka; Kamada, Yoshihiro; Maeda, Haruka; Sobajima, Tomoaki; Hikita, Hayato; Iijima, Masumi; Okamoto, Yuta; Misaki, Ryo; Fujiyama, Kazuhito; Nagamori, Shushi; Kanai, Yoshikatsu; et al.
Abstract: The functions of cell surface proteins, such as growth factor receptors and virus/bacteria-entry receptors, can be dynamically regulated by oligosaccharide modifications. In the present study, we investigated the involvement of glycosylation in hepatitis B virus (HBV) entry into hepatoma cells. Infection of oligosaccharide-remodeling hepatoma cells with a pseudo virus of HBV, bio-nanocapsule (BNC), was evaluated by flow cytometry and confocal microscopy. Among various experiments using several hepatoma cells, marked difference was observed between Huh6 cells and HB611 cells, which were established by HBV gene transfection into hepatoma cells. Comprehensive oligosaccharide analysis showed dramatic increases of core fucosylation in HB611 cells, compared with Huh6 cells. Knock down of fucosyltransferase 8 ( FUT8 ) reduced BNC entry into HB611 cells. In contrast, overexpression of FUT8 in Huh6 cells increased BNC entry. Although expression of sodium taurocholate cotransporting polypeptide (NTCP), which is one of HBV receptors was very similar between Huh6 and HB611 cells, proteins coprecipitated with NTCP were dependent on levels of core-fucosylation, suggesting that core-fucosylation regulates BNC entry into hepatoma cells. Our findings demonstrate that core-fucosylation is an important glycosylation for HBV infection of hepatoma cells through HBV-receptor-mediated endocytosis. Down-regulation of core-fucosylation may be a novel target for HBV therapy.